Effectiveness of Ranolazine to Prevent Myocardial Injury During Elective Percutaneous Coronary Intervention - Iqbal, SM Mamun; Ahsan, Syed Ali; Jahan, Kasekh Akhtar; Eva, Sohely Nazneen (Anwer Khan Modern Medical College Journal, 2019)
Background: Ranolazine is a novel antianginal drug that reduces intracellular accumulation of calcium ion in ischemic myocardium. A pilot randomized study (n=70) has shown that pretreatment with ranolazine 1000mg twice daily for 7days significantly reduced periprocedural myocardial injury (PMI) in elective Percutaneous coronary intervention (PCI). Our objective was to detect whether similar effect could be obtained by ranolazine pretreatment through an interventional study. Materials & Methods: 110 patients with chronic stable angina scheduled for elective PCI were enrolled in an interventional study. For 7 days before the procedure, 55 patients were allocated to receive ranolazine 1000 mg twice daily (ranolazine group) and 55 patients didn't receive ranolazine (control group). Serum creatinine kinase-MB (CK-MB) and Troponin I levels were measured at baseline and 24 hours post procedure. Results: Periprocedural myocardial injury [i.e. an elevation of serum biomarkers (preferably cardiac troponins) above the 99th percentile of upper reference limit (URL)] was detected less commonly after PCI in ranolazine than in control group (11% vs. 27%, p=0.0001). Also, PCI-related myocardial infarction [i.e., post procedural increase in CK-MB>3 times above the URL] tended to be lower in the ranolazine versus placebo group: 1.8% versus 5.45%, P=0.0002. 24 hours post procedural levels of cardiac markers were also significantly lower in the ranolazine versus control group (CK-MB: 2.42±2.05 versus 7.02±9 ng/ml, P=0.001; Troponin 1: 0.447±0.74 versus 1.18±1.6 ng/ml, P=0.004). No significant adverse effect of the drug was reported. Conclusion: So, we have concluded that ranolazine was effective in significantly reducing the periprocedural myocardial injury in elective PCI. Anwer Khan Modern Medical College Journal Vol. 10, No. 1: Jan 2019, P 43-49